ENERGETIC ESTIMATION OF HEAT-RECOVERY COKE OVEN - Casemiro, R. L.; Tapanes, N. C. O.; Souza, M. C. L.; Santana, A. I. C.; Pinto, W. C. L. (Revista de Engenharia Térmica, 2022)
Worldwide, steel production insistently seeks energy strength, pointing out the precision of application of all energy from the raw material with the objective of increasing production with quality and economically viable. In this sense, the energy assessment is the basis adopted to decide on the manufacture of coke in the industry. With this argument, this paper presents an energy analysis of Heat Recovery furnaces through calorific value, a method specified by the Energy Research Company of Brazil and the Brazilian Association of Metals and Materials for application in calculations in a productive environment. The data of the basic raw materials for the production of coke, the technological analysis and the energy estimation in the manufacture of coke in Coke Ovens Heat Recovery can be found in the proposed method. The present work presents result that demonstrate that the active and efficient use of the calorific value of metallurgical coal produces an energy quality coke for the manufacture of pig iron in the blast furnace.